2006
DOI: 10.1016/j.physa.2005.08.052
|View full text |Cite
|
Sign up to set email alerts
|

Novel order parameter to describe the critical behavior of Ising spin glass models

Abstract: A novel order parameter Φ for spin glasses is defined based on topological criteria and with a clear physical interpretation. Φ is first investigated for well known magnetic systems and then applied to the Edwards-Anderson ±J model on a square lattice, comparing its properties with the usual q order parameter. Finite size scaling procedures are performed. Results and analyses based on Φ confirm a zero temperature phase transition and allow to identify the low temperature phase. The advantages of Φ are brought … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 31 publications
0
13
1
Order By: Relevance
“…They found that the fraction of solidary spins in 3D(2D) is 0.76(0.67) of the total. In contrast with what is observed in 2D [20,21], the largest component of the solidary spins in 3D does not fragment as the system size grows, involving 60% of all the spins. Furthermore, the largest component in 3D forms a compact percolating cluster [22].…”
contrasting
confidence: 83%
See 1 more Smart Citation
“…They found that the fraction of solidary spins in 3D(2D) is 0.76(0.67) of the total. In contrast with what is observed in 2D [20,21], the largest component of the solidary spins in 3D does not fragment as the system size grows, involving 60% of all the spins. Furthermore, the largest component in 3D forms a compact percolating cluster [22].…”
contrasting
confidence: 83%
“…This structure can be used to divide the spins in the system in two sets: solidary spins, which are the spins in the backbone and thus maintain their relative orientation in all the ground-state configurations, and non-solidary spins which are simply all the spins that are not in the backbone [11]. Further insight in the static properties of the 3D and 2D EA model has been recently addressed by Romá et al [21,22]. They found that the fraction of solidary spins in 3D(2D) is 0.76(0.67) of the total.…”
mentioning
confidence: 99%
“…It is worth stressing that usually one is interested in studying the outof-equilibrium properties below the critical temperature T c . However, in the two-dimensional EA spin glass model T c 0 [21,22]. Nevertheless, it is widely accepted that for low enough temperatures, the dynamics remains out of equilibrium at short times and is very similar to the one observed in three-dimensional spin glasses [12,23].…”
mentioning
confidence: 89%
“…20,21 Using a parallel tempering Monte Carlo algorithm it is possible to systematically arrive at GS configurations, 22 which are necessary to determine the rigid lattice. We stress that the determination of this structure for each disorder realization requires to visit O͑N͒ times the GS.…”
Section: Modelmentioning
confidence: 99%